Music on stamps - Mickleburgh, Roy (International Library of African Music, 1960)
During the past forty years a number of countries have issued postage stamps to commemorate famous composers, musicians, conductors, music festivals, and even national anthems. One of the earliest European issues was in 1922 when a set of Austrian Charity stamps were on sale for a short period in aid of a Musicians Fund. There were seven different values bearing portraits of Haydn, Mozart, Beethoven, Schubert, Bruckner, Strauss and Wolf. Some countries have issued stamps depicting musical instruments and some interesting examples have appeared showing musicians playing traditional instruments of their particular country. In 1931 the Belgian Congo issued a set of three stamps showing native flute players (40c. green) native musicians—to quote the Stamp Catalogue, (50c. violet) and native drummers (60c. purple).
Keywords: Ethnomusicology; Musicians; African Music; Postage Stamp; Belgian Congo